Analisis keamanan steganografi teks dengan metode lsb (least significant bit) pada citra digital - Aqilah Syaima' Fadel; Rianto David Saputra; Fatma, Yulia; Risky Nanda Putra (Computer Science and Information Technology, 2024)
The rapid development of technology makes it possible for unauthorized parties to extract messages from cover media. Therefore, additional security measures are required to protect the hidden message. Previous research has proposed combining steganography and cryptography techniques. Cryptography, as a technique for securing messages, can be classified into modern and classical based on the time it emerged. The key types include symmetric and asymmetric cryptography with some popular algorithms such as Rivest Cipher 4 (RC4), Data Encryption Standard (DES), and Advanced Encryption Standard (AES). Steganography, which is the art and science of hiding messages, is important for maintaining the confidentiality and security of data and information. Despite the advantages of sending data over the internet, there are disadvantages such as cybercrime, including eavesdropping and data alteration. The Least Significant Bit (LSB) method is a well-known strategy in steganography, mainly by using the LSBs of image pixel data. This method provides high security and can customize embedding techniques without information loss due to compression and invisible changes in image steganography. The importance of using a lossless compression format when using the LSB method is illustrated in stego image compression. The use of compression formats that suffer from loss (lossy) can result in the loss of the secret message. Although LSB steganography is commonly used due to its simplicity, it is vulnerable to detection by sophisticated steganographic analysis algorithms. This research highlights the limitations in information hiding capacity and security risks that need attention.